Students’ Perceptions of Direct Instruction in Learning Subject–Verb Agreement in Writing - Ahmad Yusri; Laila Wati (Indonesian Journal of Innovation in Education Research, 2026)
This study aims to investigate students’ perceptions and identify the benefits and difficulties experienced by students when learning subject–verb agreement through Direct Instruction. The method used in this research used a qualitative descriptive study. The participants were 35 students from the English Education Department of Universitas Hamzanwadi. The data were collected using questionnaires. The findings showed that the Direct Instruction Model was useful for teaching subject–verb agreement because clear explanations, examples, demonstrations, guided practice, and feedback helped students understand and apply the rules, particularly in simple sentences. This study concludes that the Direct Instruction Model improved students’ understanding, carefulness, interest, and confidence in writing. However, more guided practice, contextual exercises, paragraph writing, and self-editing activities are needed to help students apply subject–verb agreement consistently. Since the study used a questionnaire, the findings reflected students’ perceptions rather than direct improvements in writing performance